Lean Manufacturing and Operational Performance: An Empirical Study on an Apparel Manufacturing Company - De Silva, Pubudika Isurini; Seneviratne, S M Chaturika (Universitas Syiah Kuala, 2022)
Purpose Thepresent study aims to explore how a firm implements lean management practices by utilizing firm specific resources and their influence on the operational performance of an apparel manufacturing company.Design/Methodology/approach The paper uses a single case, in depthstudy approach based on a Sri Lankan apparel manufacturing company. Data are collected using interviews, observations and documentary evidence.Findings The research study found that lean manufacturing considerably impacts to enhance the firms operational performance throughimproved quality, reduced cost, improved safety, increased speed, and improved moral. The case data suggested around twenty-five lean practices suitable to be implemented by a selected apparel manufacturing company and gain a competitive advantage in the contemporary market. Through the analysis, it was found that contribution of organizational resources and technology resources of a firm are essential to sustain the gained competitive advantage through lean manufacturing, confirmed by the assessment of the criteria of value, rare, inimitability and non-substitutability.Research Limitations/Implications As the research is directed towards the apparel manufacturing industry in Sri Lanka, the applicability of the findings may cause adversity for other manufacturing industries, broadening the scope of future research.Practical Implications As an extension to the lean manufacturing compositions, the findings of the study will have pragmatic implications tooperational managers and executives involved in developing and implementing lean strategies, particularly in terms of applicable lean practices and key strategic resources to sustain the competitive edge through lean implementation.Originality/Value This study contributes to the literature on strategic management by documenting the impact of lean manufacturing on operational performance in the Sri Lankan context through Resource-Based View approach, such interrelated theoretical insights are vital to gain a sustained competitive advantage.